Kesejahteraan Psikologis Wanita Lajang di indonesia - Mulyani, Ailia; Yunita Sari (UNISBA Press, 2024)
Abstract. The number of singlehood increases every year in Indonesia. Stigma is an inherent part of singlehood. People often label singlehood as spinsters or unmarketable. This can affect the psychological well-being of singlehood. This study aims to explore articles on psychological well-being in single women in Indonesia using the scoping review method. The researcher searched for articles related to the research theme on Google Scholar, Scopus, Sagepub and SpringerLink. Articles with themes related to the psychological well-being of singlehood were obtained with publications in the time span of 2012 to 2023 in the form of Indonesian and English scientific articles. A total of 50 articles were identified from the searches in the four databases. After selection, the number of articles used in this study was 11. The results of several articles show that the stigma circulating in society affects the psychological well-being of singlehood. In addition, psychological well-being in single women is influenced by loneliness and perceived social support. Loneliness is felt in the form of anxiety and feeling uncomfortable with their single status. Loneliness and depression are also experienced by single women due to the negative stigma from society. In addition, factors that affect psychological well-being are good social relations, having productive activities, support from family and the surrounding environment. Abstrak. Peningkatan angka melajang terjadi setiap tahunnya di Indonesia. Stigma merupakan bagian yang melekat pada wanita lajang. Masyarakat sering kali menjuluki wanita lajang sebagai perawan tua ataupun tidak laku. Hal tersebut dapat mempengaruhi kesejahteraan psikologis wanita lajang. Penelitian ini bertujuan untuk mengeksplorasi artikel mengenai kesejahteraan psikologis pada wanita lajang di Indonesia dengan menggunakan metode scoping review. Peneliti mencari artikel-artikel yang berkaitan dengan tema penelitian pada Google Scholar, Scopus, Sagepub dan SpringerLink. Artikel-artikel dengan tema terkait kesejahteraan psikologis wanita lajang didapatkan dengan publikasi dalam rentang waktu 2012 hingga 2023 berbentuk artikel ilmiah berbahasa Indonesia maupun Inggris. Total 50 artikel diidentifikasi dari penelusuran di empat database. Setelah melakukan seleksi, jumlah artikel yang digunakan dalam penelitian ini adalah 11 artikel. Hasil dari beberapa artikel menunjukan bahwa stigma yang beredar di masyarakat mempengaruhi kesejahteraan psikologis wanita lajang. Selain itu kesejahteraan psikologis pada wanita lajang dipengaruhi oleh kesepian dan dukungan sosial yang dirasakan. Kesepian dirasakan dalam bentuk cemas dan merasa tidak nyaman dengan status lajangnya. Rasa kesepian dan tertekan juga dialami wanita lajang akibat adanya stigma negatif dari masyarakat. Selain itu faktor yang mempengaruhi kesejahteraan psikologis yaitu relasi sosial yang baik, memiliki kegiatan yang produktif, dukungan dari keluarga dan lingkungan sekitar.